2009
DOI: 10.1038/bmt.2009.119
|View full text |Cite
|
Sign up to set email alerts
|

Safety and preliminary efficacy of plerixafor (Mozobil) in combination with chemotherapy and G-CSF: an open-label, multicenter, exploratory trial in patients with multiple myeloma and non-Hodgkin's lymphoma undergoing stem cell mobilization

Abstract: Plerixafor, a novel CXCR4 inhibitor, is effective in mobilizing PBSCs particularly when used in conjunction with G-CSF. In four cohorts, this pilot study explored the safety of plerixafor mobilization when incorporated into a conventional stem cell mobilization regimen of chemotherapy and G-CSF. Forty (26 multiple myeloma and 14 non-Hodgkin's lymphoma) patients were treated with plerixafor. Plerixafor was well tolerated and its addition to a chemo-mobilization regimen resulted in an increase in the peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 15 publications
2
93
0
Order By: Relevance
“…In the largest feasibility study published, addition of plerixafor to CT þ G-CSF mobilisation resulted in a mean two-fold increase in myeloma patients and 2.15-fold increase in NHL patients in the number of CD34 þ cells collected when compared with the collection on the day of plerixafor administration. 79 In a small group of patients who mobilized poorly with chemomobilization, a several fold increase in blood CD34 þ counts after plerixafor has been reported, 80,81 further evidence supporting the superior potential for this combination. The triple combination is the obvious choice whether very high CD34 þ collection yields are needed.…”
Section: Effect Of Mobilization Regimen On Graft Characteristicsmentioning
confidence: 93%
“…In the largest feasibility study published, addition of plerixafor to CT þ G-CSF mobilisation resulted in a mean two-fold increase in myeloma patients and 2.15-fold increase in NHL patients in the number of CD34 þ cells collected when compared with the collection on the day of plerixafor administration. 79 In a small group of patients who mobilized poorly with chemomobilization, a several fold increase in blood CD34 þ counts after plerixafor has been reported, 80,81 further evidence supporting the superior potential for this combination. The triple combination is the obvious choice whether very high CD34 þ collection yields are needed.…”
Section: Effect Of Mobilization Regimen On Graft Characteristicsmentioning
confidence: 93%
“…Recent publications have found that plerixafor is safe and efficacious when added to chemotherapy mobilization and may accelerate the rate of increase in CD34 þ cells collected, 12 as well as rescue poor mobilizers. 13 Future studies will be needed to define algorithms for using plerixafor after chemotherapy mobilization and also to assess cost and resource utilization of this approach.…”
Section: Discussionmentioning
confidence: 99%
“…44 Currently, plerixafor is used for mobilization of stem cells in patients with non-Hodgkin lymphoma or multiple myeloma. [45][46][47] It has been shown that microenvironmental Cxcl4 derived from MKs regulates HSC cell cycle activity. Using transgenic inducible diphtheria toxin receptor mice (where MKs are depleted by inducible diphtheria toxin receptor expression) crossed with Cxcl4-cre mice, Bruns et al 16 showed that short-term (7 days) depletion of Cxcl4 led to an increase in HSC proliferation, a 4.6-fold increase in HSC numbers, and enhanced reconstitution following a single transplantation.…”
Section: Discussionmentioning
confidence: 99%